Steinernema brazilense n. sp (Rhabditida: Steinernematidae), a new entomopathogenic nematode from Mato Grosso, Brazil - Nguyen, Khuong B.; Ambros Ginarte, Carmen M.; Leite, Luis G.; dos Santos, Jaime M. [UNESP]; Harakava, Ricardo (Academic Press Inc. Elsevier B.V., 2010)
A new entomopathogenic nematode, Steinernema brazilense n. sp., was isolated from a single soil sample collected from a natural forest in Mato Grosso do Sul state, Brazil. S. brazilense n. sp. is characterized morphologically by features of infective juveniles (IJ), males and females. For the IJ, body length averaging 1157 (1023-1284) mu m, distance from anterior end to excretory pore 95 (87-102) mu m, from anterior end to end of esophagus 148 (139-153) mu m, tail length 85 (80-104) mu m, D% and E% values 63 (58-70) and 106 (95-118.0), respectively. Lateral field pattern variable; the formula for the arrangement of ridges from head to tail is: 2, 4, 6, 8, 6, 2. For the male, the diagnostic characters include spicule averaging 83 (75-89) mu m; D% about 65; the ratio SW% about 192. The length of spicule head is greater than width. Lateral field with one narrow ridge. First generation females are characterized by the presence of a ventral postanal swelling. S. brazilense n. sp. is morphologically close to Steinernema diaprepesi. It can be differentiated from S. diaprepesi by its longer IJ body length (1157 vs 1002 mu m), longer distance from anterior end to excretory pore (1110 vs 75 mu m), a longer tail length (103 vs 83 mu m); males of the new species with longer spicule (83 vs 79 mu m). The new species can be distinguished further from other members of Steinernema glaseri group by characteristics of rDNA of ITS and D2D3 regions. Published by Elsevier B.V.
Keywords: D2D3; Entomopathogenic nematodes; ITS; Molecular; Morphology; Phylogeny; SEM; Taxonomy